2015
DOI: 10.1590/1807-3107bor-2015.vol29.0107
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of two reciprocating instruments using bending stress and cyclic fatigue tests

Abstract: The aim of this study was to comparatively evaluate the bending resistance at 45º, the static and dynamic cyclic fatigue life, and the fracture type of the WaveOne (Dentsply Maillefer, Ballaigues, Switzerland) 25-08 and Reciproc (VDW, Munich, Germany) 25-08 instruments. A total of 60 nickel-titanium (NiTi) instruments (30 Reciproc and 30 WaveOne) from three different lots, each of which was 25 mm in length, were tested. The bending resistance was evaluated through the results of a cantilever-bending test condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…6 Oxide particles derived from the manufacturing process can act as nucleation sites for the formation of microvoids, leading to dimpled ruptures and subsequent instrument fracture. 13,15,29 In the present study, crack propagation and connected pitted regions were clearly observed in both instruments after the second use, with a greater predominance in the WaveOne instruments (Figure 3a-d). In a previous SEM study, the propagation of cracks parallel to the local fluting orientation under connected pitted regions had been observed on the surfaces of used NiTi instruments.…”
supporting
confidence: 55%
“…6 Oxide particles derived from the manufacturing process can act as nucleation sites for the formation of microvoids, leading to dimpled ruptures and subsequent instrument fracture. 13,15,29 In the present study, crack propagation and connected pitted regions were clearly observed in both instruments after the second use, with a greater predominance in the WaveOne instruments (Figure 3a-d). In a previous SEM study, the propagation of cracks parallel to the local fluting orientation under connected pitted regions had been observed on the surfaces of used NiTi instruments.…”
supporting
confidence: 55%
“…On the contrary with these results, Pedullà et al27 have determined no difference between RPC and WO files. In the studies, the reason for higher cyclic fatigue resistance of RPC files than WO has been shown to be the differences between the cross section and core structures of files 13252829. On the contrary with WO, we believe that WOG files had similar fatigue life values with RPC because of the new alloy and production method of WOG.…”
Section: Discussionmentioning
confidence: 89%
“…In the literature, there are many studies comparing the cyclic fatigue resistances of WO files, which have been used before WOG files, and RPC files at different angles of curvature 13252627. In their study, Scelza et al25 have compared the cyclic fatigue resistance of RPC and WO files, and found that of RPC to be higher.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One hypothesis explaining why flexural fatigue occurs is that the grinding process across the grains of a NiTi wire reduces the overall strength of the instrument, owing to the formation of machining defects along its flute surfaces, and to the build-up of residual stress within its internal structure (Tripi et al 2006). This may be attributed to oxide particles that originate from the manufacturing process and act as nucleation sites for the formation of microvoids, which could lead to dimpled ruptures with subsequent material failure (Kuhn et al 2001, Cheung & Darvell 2007, Kim et al 2012, Scelza et al 2015.…”
Section: Introductionmentioning
confidence: 99%